Anticancer therapy-induced adverse drug reactions in children and preventive and control measures - Yan, Hui; Wang, Penggao; Yang, Fang; Cheng, Weyland; Chen, Congcong; Zhai, Bo; Zhou, Yang (Frontiers in Pharmacology, 2024)
In recent years, considerable achievements have been made in pediatric oncology with the innovation and development of antitumor drugs. However, compared to adults, children as a special group have not yet matured fully in terms of liver and kidney function. Moreover, pediatric patients are prone to more adverse drug reactions (ADRs) from the accumulation of antineoplastic drugs due to their smaller body size and larger body surface area. Chemotherapy-related ADRs have become a non-negligible factor that affects cancer remission. To date, studies on ADRs in pediatric cancer patients have emerged internationally, but few systematic summaries are available. Here, we reviewed the various systemic ADRs associated with antitumor drugs in children and adolescent patients, as well as the advances in strategies to cope with ADRs, which consisted of neurotoxicity, hematological toxicity, cardiotoxicity, ADRs of the respiratory system and gastrointestinal system and urinary system, ADRs of the skin and its adnexa, allergic reactions, and other ADRs. For clinicians and researchers, understanding the causes, symptoms, and coping strategies for ADRs caused by anticancer treatments will undoubtedly benefit more children.